Bioanalytical separation and preconcentration using ionic liquids - Escudero, Leticia Belén (2013)
Ionic liquids (ILs) are novel solvents that display a number of unique properties, such as negligible vapor pressure, thermal stability (even at high temperatures), favorable viscosity, and miscibility with water and organic solvents. These properties make them attractive alternatives to environmentally unfriendly solvents that produce volatile organic compounds. In this article, a critical review of state-of-the-art developments in the use of ILs for the separation and preconcentration of bioanalytes in biological samples is presented. Special attention is paid to the determination of various organic and inorganic analytes - including contaminants (e.g., pesticides, nicotine, opioids, gold, arsenic, lead, etc.) and functional biomolecules (e.g., testosterone, vitamin B12, hemoglobin) - in urine, blood, saliva, hair, and nail samples. A brief introduction to modern microextraction techniques based on ILs, such as dispersive liquid-liquid microextraction (DLLME) and single-drop microextraction (SDME), is provided. A comparison of IL-based methods in terms of their limits of detection and environmental compatibilities is also made. Finally, critical issues and challenges that have arisen from the use of ILs in separation and preconcentration techniques are also discussed.